Retreating the standard of defendant's nationality in personal status - الامين, خير الدين (Journal of Legal Sciences, 2020)
Contemporary private international law sometimes allows parties to choose the law applicable to their personal relations. This approach is applicable at both levels: national legislation and international conventions, for example national legislation, Belgian private international law of 2004 and other laws of North American countries as well as German law. In terms of international agreements, we have noted that the Rome Statute III represents an important stage for the revision of the criterion of nationality before the will of the law of will, as this standard now determines how to reach the substantive provisions of the applicable law. The immediate aim of addressing this issue was to determine the extent to which Article 19 of the Iraqi Civil Code in force could be amended by giving the parties the possibility to determine the law applicable to their disputes, taking into account some of the known limitations of private international law, such as the notion of public order.